Balancing Strategies for Sustainable Growth in International Business - Muh. Djabir; Mozes Haryanto Baottong; Karta Negara Salam (Yayasan Vifada Cendikia Indonesia, 2025)
The purpose of this research is to investigate the critical importance of adopting a holistic approach to sustainable growth in international business. Through a comprehensive review of existing literature, this study examines the integration of economic, environmental, and social dimensions into business decision-making processes, with a focus on corporate sustainability initiatives, technological innovation, and stakeholder engagement. The research design and methodology involve a systematic analysis of theoretical frameworks, empirical studies, and case examples to elucidate key concepts and identify emerging trends in the field. Findings suggest that adopting a triple-bottom-line approach, which incorporates economic, environmental, and social considerations, is crucial for achieving sustainable growth and resilience in today's interconnected global economy. Corporate sustainability initiatives play a vital role in aligning business strategies with principles of sustainable development, enabling businesses to enhance reputation, build trust with stakeholders, and drive innovation. The implications of this research underscore the need for businesses to embrace sustainability as a core principle and integrate sustainability considerations into core business operations. By leveraging technological innovation, fostering stakeholder engagement, and promoting responsible consumption, businesses can contribute to a more sustainable and prosperous future for all.